An Examination of Dynamic Stall Vortex Inception on a Finite Wmg - Ferrecchia, Antonella; N. Coton, Frank; Galbraith, Roderick A. McD. (Universiti Putra Malaysia Press, 2000)
In the present study, the behaviour of the vorticity flux on a wing of NACA 0015 cross section was analysed for ramp-up motion over a range of dimensionless pitch rates. The variations in the vorticity flux were examined as a means to identify the role of the vorticity leaving the boundary layer in the initiation, development and growth of the dynamic stall vortex. It has been found that there are two main sources of bipolar vorticity located within the first 3% of the chord at all span wise stations on the wing. These sources move and change strength as the wing is pitched through the incidence range. One factor that influences their behaviour is the reduced pitch rate and this effect is discussed. Further, it is shown that there is an apparent link between the negative source of vorticity and the first observable manifestation of the dynamic stall vortex on the pressure distribution near the mid-span.